Application of Expansion and Retrenchment Strategies: A Case Study of Zain Group - Maryam Alsbaity; Ulfa Alvianti; Sindy Hengkeng; Siti Hajar Nurlaila (Journal of International Conference Proceedings (JICP), 2018)
Zain Group is a telecommunication company based in Kuwait. Zain has been dealing with many problems in its supply chain, especially its geographic divisions. the decisions made for growth and defense were applied with poor vision and strategy, poor management and strategic decision making process, In addition to economic, political, social, technological and legal factors which led to a decrease in Zain's financial performance. This paper analyzes the issues of Zain's application of the expansion and retrenchment strategies and aims to advocate alternative solutions regarding its divisions as a part of the supply chain. Based on the data collected and analyzed for the period 2012-2016, this paper shall Employ descriptive analysis, and Quantitative analysis (e.g. Market Cap., Market Share, Financial Ratios).The branches of Zain Group that shall be the focus of our study are spread in eight geographic divisions (Kuwait, Saudi Arabia, Jordan, Lebanon, Morocco, Bahrain, Iraq, South Sudan, Sudan). The Findings of the research indicates that great strategic management and better understanding of environmental factors have a groundbreaking impact on the Groups overall performance. Keywords: Divisions, Expansion, Kuwait, Management, Retrenchment, Strategy, Telecommunication, Zain Group.